Treatment of cauliflower seeds with product based on bacillus subtilis aiming plant seedling production, development and productivity. - de Souza, Emanuele Possas [UNESP]; Marques, Sheury Celante [UNESP]; Lourenço, Flávia Mendes Dos Santos [UNESP]; de Sá, Marco Eustáquio [UNESP]; Freitas, Pâmela Gomes Nakada [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2024)
The relation between seed vigor and field performance is not yet fully understood, and it is questionable whether these effects extend to more advanced phenological stages and if they affect crop production. In front of that, the objective of this study was to evaluate the effects on the seedlings and plant production of cauliflower using doses of product based on Bacillus subtilis in seed treatment. The study was conducted in Ilha Solteira city, São Paulo State. The experimental design was a complete randomized design for laboratory analysis and complete randomized blocks for the field stage. Ten treatments were studied in a 2 x 5 factorial scheme with four replications. The treatments consisted of seed treatment of cultivars Sharon and Barcelona with Bacillus subtilis-based product (strain FMT001 containing 3x108 cells cm-3) in five doses (0, 100, 200, 300 and 400 mL per 10 kg of seeds). Seed vigor and crop yield (shoot, root and inflorescence weight, leaf number, inflorescence diameter and yield) characteristics were evaluated. Cultivars averages were compared by Tukey test (p <0.05) and regression for the doses. The results showed that doses of 200 and 400 mL per 10 kg of seeds increased the percentage of strong seedlings of cultivars Barcelona and Sharon, respectively.
Keywords: Biological treatment; Brassica oleracea var. botrytis; Vegetable; Vigor